Good Government Governance, Gaya Kepemimpinan dan Kinerja Manajerial Penyelenggara Pemerintahan Desa - Nanda, I Gusti Ayu Agung Yustika; Putri, I Gusti Ayu Made Asri Dwija (E-Jurnal Akuntansi, 2021)
This study aims to examine the effect of the implementation of Good Government Governance and leadership style on managerial performance of village government administrators in Badung Regency. Based on the results of the analysis it was found that the variables of Good Government Governance and leadership style simultaneously had a significant effect on managerial performance. This shows that the better the implementation of Good Government Governance and the right leadership style, the better managerial performance will be. Good Government Governance partially has a significant effect on managerial performance. This shows that the existence of good governance can improve managerial performance. Leadership style also partially has a significant effect on managerial performance. This shows that the right leadership style can improve managerial performance. Keywords: Good Government Governance; Leadership Style; Managerial Performance.